Assessment of sunflower hybrid yield in southern Sonora - Cantúa-Ayala, Jesús Antonio; Borbón-Gracia, Alberto; Marroquín-Morales, José Ángel; Castillo-Torres, Nemecio (Revista Mexicana de Ciencias Agrícolas, 2025)
The sunflower (Helianthus annuus L.) is native to North America, originating in the southwestern United States of America and northern Mexico; the seed oil of sunflower varieties is considered of good quality for edible purposes. Likewise, limited water availability is a recurring problem in irrigation districts in southern Sonora, forcing producers to look for low-water crop options for the autumn-winter agricultural cycle; in this sense, sunflower is a crop with a low demand for water. The study aimed to identify sunflower hybrids, which would allow them to be suggested for planting to producers in southern Sonora. The trial was carried out in the 2020-2021 autumn-winter agricultural cycle. Commercial high oleic hybrids were used. The following agronomic characteristics were recorded: start and development of the flower bud, start and end of flowering, physiological maturity, plant height, weight of 100 seeds, hectoliter weight, and grain yield. The sunflower hybrid SYN 3 950 HO had yields of 3 362 and 3 596 kg ha-1, Cobalt II HO of 2 634 and 3 058 kg ha-1, and Daytona CL of 2 281 and 2 545 kg ha-1. The yields obtained from the sunflower hybrids evaluated allow us to suggest them for planting to producers in southern Sonora.